Community radio-based disaster information dissemination pattern on K-Pass FM Radio Katapang - Ute Lies Siti Khadijah; Franck Lavigne; Sapari Dwi Hadian; Rully Khairul Anwar; Dian Wardiana Sjuchro; Edwin Rizal; Lutfi Khoerunnisa (Jurnal Kajian Informasi dan Perpustakaan, 2022)
K-Pass FM Radio Katapang is one of the radios disseminating information about disasters that focuses on training, awareness, and understanding of the people of Katapang Regency to play a role in dealing with disasters and help reduce disaster risk as well. This study aimed to determine the dissemination pattern of disaster information based on community radio conducted by Radio K-Pass FM Katapang. The research used a qualitative approach through case studies research methods. Data collection techniques included in-depth interviews, observation, documentation, and literature studies. Informants amount six people consist of resource persons consisting of community radio administrators, people who feel the impact of the existence of community radio, and people who take part in community radio programs. The study results showed that the dissemination of disaster information on Radio K-Pass FM Katapang increased the awareness of the local community about the dangers of disasters. The disaster information on K-Pass FM Radio Katapang went through three stages: the pattern of dissemination of disaster mitigation information (pre), the pattern of disseminating information when the disaster occurred (in), and post-disaster information (past). This community radio also established a Rescue School that aims to provide knowledge and actions that the community can carry out when a disaster occurs. This study concludes that Radio K-Pass FM Katapang has succeeded in becoming a community radio that positively impacts society, especially in disseminating information related to disasters. Therefore, Radio K-Pass FM Katapang still exists today even though it has been around for a long.